The role of computed tomography scans in diaphyseal femur fractures following gunshot injuries: A survey of orthopaedic traumatologists. Issue 12 (December 2017) - Hwang, John S.; Gibson, Peter D.; Koury, Kenneth L.; Stekas, Nicholas; Sirkin, Michael S.; Reilly, Mark C.; Adams, Mark R.
Abstract: The objective of this study was to analyze if the addition of CT changed the management of femoral shaft fractures caused by gunshot wounds when compared to those managed with plain radiography alone. Methods: A multiple-choice, single-answer electronic survey was created to compare utility of advanced imaging when treating femur fractures resulting from gunshot injury. A total of ten femoral shaft fracture cause by gunshot injuries were selected for an online survey to be administered to orthopeaedic traumatologists. The survey compared the use the of fixation device and surgical planning before and after the CT scan. Results: A total of 99 surveys were initiated, of which 82 were completed. For proximal shaft fractures, 37% of experts reported that a CT scan should be ordered based on the radiograph alone, prior to reviewing the CT. After reviewing the CT, 5% of experts reported that they would have performed a "major" change, and 10% reported that they would have performed a "minor" change. 4% of surveyors would have changed their decision regarding ordering a CT. For distal femoral shaft fractures, 42% of experts selected that a CT scan would have been ordered prior to reviewing the CT. After reviewing the CT, 2% would have performed a "major" change, and 8% would have performed a "minor" change in management. 5% of surveyors would have changed their decision regarding ordering a CT. Conclusion: Our study demonstrated that CT scans are relatively unlikely to cause major changes in fracture management of gunshot-induced fractures of femoral shaft.